STRATEGI MEDIA RELATIONS HUMAS UNIVERSITAS IBN KHALDUN BOGOR DALAM MENINGKATKAN CITRA POSITIF LEMBAGA - Zahara Aulia Rahmah; Kamalludin; Retno Triwoelandari (Universitas Pahlawan Tuanku Tambusai, 2022)
In the reformation era, mass media has become one of the most effective tools to convey information to a wide audience. So Public Relations, which functions as a bridge of information between institutions and the community, uses the media as a tool to disseminate information and improve a positive image for the institution, this is done through media relations. This study aims to determine the media relations of Ibn Khaldun University Bogor Public Relations in increasing the positive image of the institution. This study uses descriptive qualitative methods, and data collection techniques used are observation, interviews, and documentation. The results show that the Public Relations of Ibn Khaldun University Bogor in implementing the media relations has implemented five strategies, namely, 1) providing service to the media according to what is needed, 2) building a reputation so that it can be trusted by providing information from experts or sources who can be trusted and in accordance with their fields, 3) provide good information scripts, and are supported by photos and videos to complement the information provided to media partners, 4) cooperate in providing the information needed by media partners, 5) provide verification facilities to meet the satisfaction of the media partners. media partners to the information they want to know. Keywords: Strategy Media Relations, Public Relations of Ibn Khaldun University Bogor, Positive Image.